1990
DOI: 10.1063/1.102641
|View full text |Cite
|
Sign up to set email alerts
|

Study of the interface of undoped and p-doped ZnSe with GaAs and AlAs

Abstract: We have used electrolyte electroreflectance (EER) to characterize ZnSe/GaAs and ZnSe/AlAs interfaces. The great sensitivity of EER to interface space-charge regions enabled us to detect both interface crossover transitions and transitions to triangular-well interface states. The observation of these transitions provides the first unambiguous proof that the ZnSe/GaAs interface is type I and allowed us to determine the band offsets and band bendings, the diffusion lengths across each interface, and the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 7 publications
2
19
0
Order By: Relevance
“…11 The molecular beam epitaxial growth of thin layers of ZnSe on GaAs results in new charge distribution at the interface, the diffusion of Zn as an acceptor into GaAs and Ga as a donor into ZnSe during sample growth. This produces an intrinsic band-bending at the interface 12 It is known that in highly doped polar semiconductors the plasma oscillation and the bulk LO phonons couple via their macroscopic electric fields. 13 The coupled modes split into two branches for a donor-doped semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…11 The molecular beam epitaxial growth of thin layers of ZnSe on GaAs results in new charge distribution at the interface, the diffusion of Zn as an acceptor into GaAs and Ga as a donor into ZnSe during sample growth. This produces an intrinsic band-bending at the interface 12 It is known that in highly doped polar semiconductors the plasma oscillation and the bulk LO phonons couple via their macroscopic electric fields. 13 The coupled modes split into two branches for a donor-doped semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that band bending at the junction of two dissimilar semiconductors can lead to new electronic states. 9 " 0 Recently we reported on the observation of such a state in ZnSe-GaAs(001) heterostructures when we used second-harmonic generation (SHG). 4 The secondharmonic spectral feature, at 2.72 eV, results from a virtual transition between the ZnSe valence band and a resonance state of a quantum well located across the junction in the GaAs conduction band.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jackson and Seebauer' 2 have shown that such a WKB approach is more reliable than a laminar approach such as that of ref. 7 under essentially all conditions.…”
Section: Introductionmentioning
confidence: 98%